Audit on Prolactin Monitoring for Patients on Oral/Intramuscular Risperidone and Intramuscular Paliperidone - Meekha Suresh (BJPsych Open)
Aims: Risperidone is a commonly used antipsychotic drug in the LD population. One of its common side effects is hyperprolactinemia, which can cause a range of symptoms. Women may experience oligomenorrhoea, amenorrhoea, galactorrhoea (breast milk production), and decreased libido. Men may experience decreased libido, erectile dysfunction, gynaecomastia, infertility, decreased bone mass, and galactorrhoea. These symptoms may go unnoticed in the LD population and lead to behavioural changes.